PENGARUH SUKU BUNGA DAN NILAI TUKAR TERHADAP HARGA SAHAM PT. BANK RAKYAT INDONESIA (PERSERO) DI BURSA EFEK INDONESIA TAHUN 2017-2021 - Nehe, Nani Karlina (Jurnal Ilmiah Mahasiswa Nias Selatan, 2024)
This research aims to determine the effect of interest rates and exchange rates on PT share prices. Bank Rakyat Indonesia (Persero) on the Indonesian Stock Exchange in 2017-2021. The type of research used is associative quantitative research. The data analysis used is multiple linear regression analysis. The results of this research show that interest rates and exchange rates have an effect on stock prices . Furthermore, in this research, a multiple linear regression analysis equation was obtained, namely: Y = 6,416,190 + (–2,771)X1 + (– 419,382)X2, meaning the constant value is 6,416,190. This shows that if the interest rate (X1) and exchange rate (X2) variables are zero, then the share price (Y) is 6,416.190. The interest rate regression coefficient (X1) is -2.771. This shows that if the interest rate (X1) increases by 1 unit or 100%, then the value of the share price variable (Y) will decrease by -2.771 assuming the other independent variables are constant. With this negative influence, it means that interest rates and stock prices show an influence.